Hsa_Circ_0001860 Promotes Smad7 to Enhance MPA Resistance in Endometrial Cancer via miR-520h - Yuan, Shuang; Zheng, Panchan; Sun, Xiao; Zeng, Judan; Cao, Wenjiao; Gao, Wuyuan; Wang, Yudong; Wang, Lihua (Frontiers in Cell and Developmental Biology, 2021)
Background: Medroxyprogesterone acetate (MPA) is one of the most commonly prescribed progestin for the treatment of endometrial cancer (EC). Despite initial benefits, many patients ultimately develop progesterone resistance. Circular RNA (circRNA) is a kind of noncoding RNA, contributing greatly to the development of human tumor. However, the role of circular RNA in MPA resistance is unknown. Methods: We explored the expression profile of circRNAs in Ishikawa cells treated with (ISK/MPA) or without MPA (ISK) by RNA sequencing, and identified a key circRNA hsa_circ_0001860. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to verify its expression in MPA-resistant cell lines and tissues. CCK8, transwell and flow cytometry were used to evaluate the functional roles of hsa_circ_0001860 in MPA resistance. The interaction between hsa_circ_0001860 and miR-520h was confirmed by bioinformatics analysis, luciferase reporter assay and RNA pull-down assay. Results: The expression of hsa_circ_0001860 was significantly downregulated in MPA-resistant cell lines and tissues, and negatively correlated with lymph node metastasis and histological grade of EC. Functional analysis showed that hsa_circ_0001860 knockdown by short hairpin RNA (shRNA) promoted the proliferation, inhibited the apoptosis of Ishikawa cells and promoted the migration and invasion of Ishikawa cells treated with MPA. Mechanistically, hsa_circ_0001860 promoted Smad7 expression by sponging miR-520h. Conclusion: Hsa_circ_0001860 plays an important role in the development of MPA resistance in EC through miR-520h / Smad7 axis, and it could be targeted to reverse the MPA resistance in endometrial cancer.